In silico Characterization of the Heme Oxygenase 1 From Bottlenose Dolphin (Tursiops truncatus): Evidence of Changes in the Active Site and Purifying Selection - Reyes-Ramos, Carlos A.; Gaxiola-Robles, Ramón; Vázquez-Medina, José Pablo; Ramírez-Jirano, Luis Javier; Bitzer-Quintero, Oscar Kurt; Zenteno-Savín, Tania (Frontiers in Physiology, 2021)
Cetacea is a clade well-adapted to the aquatic lifestyle, with diverse adaptations and physiological responses, as well as a robust antioxidant defense system. Serious injuries caused by boats and fishing nets are common in bottlenose dolphins (Tursiops truncatus); however, these animals do not show signs of serious infections. Evidence suggests an adaptive response to tissue damage and associated infections in cetaceans. Heme oxygenase (HO) is a cytoprotective protein that participates in the anti-inflammatory response. HO catalyzes the first step in the oxidative degradation of the heme group. Various stimuli, including inflammatory mediators, regulate the inducible HO-1 isoform. This study aims to characterize HO-1 of the bottlenose dolphin in silico and compare its structure to the terrestrial mammal protein. Upstream HO-1 sequence of the bottlenose dolphin was obtained from NCBI and Ensemble databases, and the gene structure was determined using bioinformatics tools. Five exons and four introns were identified, and proximal regulatory elements were detected in the upstream region. The presence of 10 α-helices, three 310 helices, the heme group lodged between the proximal and distal helices, and a histidine-25 in the proximal helix serving as a ligand to the heme group were inferred for T. truncatus. Amino acid sequence alignment suggests HO-1 is a conserved protein. The HO-1 'fingerprint' and histidine-25 appear to be fully conserved among all species analyzed. Evidence of positive selection within an α-helix configuration without changes in protein configuration and evidence of purifying selection were found, indicating evolutionary conservation of the coding sequence structure.